Organizational Politics and Employee Performance: Evidence from Pharmaceutical and Healthcare Product Manufacturing Industry - Ahmed walugembe (Journal of Management and Science, 2025)
Organizational politics presents significant challenges in the workplace, yet many employers lack clear strategies for managing its complexities. Failure to address political behaviour within acceptable limits can erode organizational competitiveness and performance. This study investigates the impact of organizational politics on employee performance at Sonacrest Healthcare Nigeria Plc, a major player in the healthcare manufacturing sector. The study focuses on three dimensions of organizational politics lobbying, withholding relevant information, and sustaining influence and control and their effects on employee adherence to administrative standards, efficiency, and quality of work. Using a survey research design, data were collected from 225 randomly selected employees out of a population of 606 through structured questionnaires. Path analysis revealed that lobbying has a significant positive effect on administrative standards, suggesting that political engagement may help formalize organizational procedures. Conversely, withholding information negatively impacts employee efficiency, highlighting the need for transparent communication systems. Sustaining influence and control was found to positively influence work quality, likely due to high-performance expectations set by those in power. The findings underscore the dual nature of organizational politics—its potential to enhance or hinder performance. The study recommends the implementation of inclusive policy-making channels, robust communication systems, and balanced leadership approaches to harness the positive aspects of organizational politics while mitigating its risks. These insights offer practical guidance for improving employee performance and organizational effectiveness in politically dynamic environments like Nigeria’s healthcare manufacturing sector.